2021
DOI: 10.1016/j.heliyon.2021.e07713
|View full text |Cite
|
Sign up to set email alerts
|

The use of Polidori's plasticity and activity charts in classifying some residual lateritic soils from Nigeria

Abstract: Over the years, Casagrande plasticity chart is mainly used to classify fine grain soils. However, the use of the plasticity chart has been questioned recently and this has led to the development of a new plasticity chart. Polidori in 2007 and 2009, respectively, developed the new plasticity and activity charts using the Atterberg's limits of pure clays (montmorillonite and kaolinite clay minerals) and their mixture with fine silica sand in different proportions. The applicability of Polidori's charts was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…To examine the effect of pretest drying temperature on the plasticity classification of the lateritic soils, the values of W L and I P in Table 3 were used to plot the points on Casagrande and Polidori [26] plasticity charts (Figures 1 and 2). It was observed that Polidori's plasticity chart gives a fair classification of lateritic soils based on soil fractions [27].…”
Section: Plasticity Chartsmentioning
confidence: 99%
“…To examine the effect of pretest drying temperature on the plasticity classification of the lateritic soils, the values of W L and I P in Table 3 were used to plot the points on Casagrande and Polidori [26] plasticity charts (Figures 1 and 2). It was observed that Polidori's plasticity chart gives a fair classification of lateritic soils based on soil fractions [27].…”
Section: Plasticity Chartsmentioning
confidence: 99%